Antineutrophil antibodies define clinical and genetic subgroups in primary sclerosing cholangitis. (13th September 2016) - Hov, Johannes R.; Boberg, Kirsten M.; Taraldsrud, Eli; Vesterhus, Mette; Boyadzhieva, Maria; Solberg, Inger Camilla; Schrumpf, Erik; Vatn, Morten H.; Lie, Benedicte A.; Molberg, Øyvind; Karlsen, Tom H.
Abstract: Background & Aims: The strongest genetic risk factors in primary sclerosing cholangitis (PSC) are encoded in the HLA complex. Antineutrophil cytoplasmic antibodies (ANCA) have been reported in up to 94% of PSC patients, but their clinical significance and immunogenetic basis are ill defined. We aimed to characterize clinical and genetic associations of ANCA in PSC. Methods: Antineutrophil cytoplasmic antibodies were analysed with indirect immunofluorescence in 241 Norwegian PSC patients. HLA‐B and HLA‐DRB1 genotyping was performed in the patients and in 368 healthy controls. Data on perinuclear ANCA (pANCA) and HLA‐DRB1 were available from 274 ulcerative colitis (UC) patients without known liver disease. Results: Antineutrophil cytoplasmic antibodies were found in 193 (80%) of the PSC patients, with pANCA in 169 (70%). ANCA‐positive patients were younger than ANCA negative at diagnosis of PSC and had a lower frequency of biliary cancer (9% vs 19%, P =.047). There were no differences between PSC patients with and without inflammatory bowel disease. Genetically, the strong PSC risk factors HLA‐B*08 (frequency in healthy 13%) and DRB1*03 (14%) were more prevalent in ANCA‐positive than ‐negative patients (43% vs 25%, P =.0012 and 43% vs 25%, P =.0015 respectively). The results were similar when restricting the analysis to pANCA‐positive patients. In UC patients without liver disease, HLA‐DRB1*03 was more prevalent in pANCA‐positive compared with ‐negative patients ( P =.03). Conclusions: Antineutrophil cytoplasmic antibodies identified PSC patients with particular clinical and genetic characteristics, suggesting that ANCA may mark a clinically relevant pathogenetic subgroup in the PSC‐UC disease spectrum.